Effect of Quantitative Structural Properties and Drug Formulation in Four Cannabinoids (Cannabidiol, Cannabigerol, Cannabichromene, and Cannabinol) on Their Lymphatic Transport after Enteral Administration in Rats - Ryšánek, Pavel; Jelínek, Petr; Housar, Hynek; Kozlík, Petr; Křížek, Tomáš; Nováková, Anežka; Sklenárová, Michaela; Paulusová, Viktória; Merdita, Sara; Arora, Mahak; Symkanych, Olesia; Šteigerová, Monika; et al. (Molecular pharmaceutics, 2025)
The effect of quantitative structural properties of drugs on the extent of lymphatic transport is not well understood. Our study aimed to describe these principles in four cannabinoids, cannabidiol (CBD), cannabigerol (CBG), cannabichromene (CBC), and cannabinol (CBN) administered as oil solutions and nanoemulsions. A series of studies in jugular vein cannulated rats and anesthetized mesenteric lymph duct cannulated rats was conducted to measure drug oral bioavailability and lymphatic transport. Log P was measured, and quantitative structural properties were correlated to the extent of lymphatic absorption. Nanoemulsion did not increase the absolute bioavailability via lymph in CBD but led to an 8-fold increase in CBG and a 3-fold increase in CBC and CBN. There was an even higher increase in the absolute bioavailability via portal vein (11-fold for CBD, 71-fold for CBG, 8-fold for CBC, and 13-fold for CBN). Relative bioavailability via lymph increased with decreasing smallest orthogonal molecular size and topological polar surface area. Nanoemulsion did not affect the total oral bioavailability but led to an increased absorption into portal blood. Intestinal lymphatic transport plays a major role in the absorption of CBD, CBG, CBC, and CBN. Planarity of the molecule and low surface polarity could be crucial structural features facilitating lymphatic transport.
Keywords: Administration, Oral; Emulsions; Male; quantitative structure−activity relationship (QSAR); potkani Sprague-Dawley; Nanoparticles; nanočástice; aplikace orální; nanoemulsion; mužské pohlaví; lymph-targeting; oral bioavailability; emulze; Cannabidiol; krysa rodu Rattus; biologická dostupnost; biologický transport; kanabinoidy; cannabinoids; Animals; Drug Compounding; pharmacokinetics; zvířata; Rats; Cannabinoids; kanabidiol; lymphatic transport; Biological Availability; příprava léků; Biological Transport; Rats, Sprague-Dawley